FEASIBILITY ANALYSIS AND DESIGN PROJECTION OF WASTE MANAGEMENT SYSTEM IN BALIKPAPAN - Ubet Khoirudin; Muslikhin Hidayat; Rochim Bakti Cahyono (Master in Systems Engineering, 2021)
Waste generation in Balikpapan from 2016 to 2020 continues to increase by 443 to 482 tons per day. One of the efforts of DLH Balikpapan is to optimize the MRF and ITF facilities, as well as to analyze how much these facilities are needed to reduce waste generation at final disposal sites (Landfill) Manggar and enhance the durability of the landfill. The approach utilized in this study employs direct observation methods, such as data collection results on the amount of waste input and output, and secondary data, such as geometric methods and all data on waste generation in Balikpapan. The calculation of the feasibility and effectiveness analysis of the MRF inorganic waste processing facility using the recovery factor approach obtained 60.3%, while the ITF organic waste processing got a result of 45.7%.With the current condition, Manggar Landfill can be used until the end of 2025, Manggar Landfill can be used until the end of 2025. By optimizing garbage processing in these two facilities, the MRF has expanded the service coverage to 3 urban villages and has a projected age of up to 2033. It will be optimized for ITF processing facilities by utilizing process biogas. The primary objective of this research is to determine how many additional processing sites are needed starting with household waste sources thus, the calculation findings show that an additional six units of MRF facilities and ten units of ITF facilities are required. As a result, with the addition of inorganic and organic waste processing sites, Manggar's Landfill estimated age is extended until 2028.